IMPLEMENTATION OF ABILITY GROUPING IN CLASS MANAGEMENT IN MADRASAH DINIYAH RAUDHATUL MUBTADIIN KRAPYAK - Rohmatun Lukluk Isnaini; Nurmalita Aulia Haz (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2022)
Placing students in classes that are not following their competencies has caused many problems, such as in the process of learning activities will be hampered. Ability grouping is one solution for grouping classes that are differentiated according to student's abilities. Thus, this research aims to determine how to implement ability grouping at Madrasa Diniyyah Raudhatul Mubtadiin Krapyak Yogyakarta. This research is descriptive qualitative research. The data collection techniques used were interviews, observations, and documentation studies. The informants consisted of 10 people: the head of the madrasa, three teachers, three guardians of students, and three students. The data obtained were analyzed through the transcript, coding, comparing and contrasting processes, and data interpretation. In achieving the validity of the data, triangulation of methods and sources is used. The results showed that 1) Ability grouping in Madrasah Diniyyah was carried out with three stages of tests, reading test, writing and memorization test. 2) The positive impacts are high self-confidence, feeling more comfortable, a spirit of competition, and making it easier for teachers to deliver the material. Then, the negative impact is feeling inferior when in the elementary class. 3) Supporting factors include support for the guardians of students, for students, and adequate infrastructure.